Peningkatan Organizational Citizenship Behavior for environment melalui Praktik Green Human Resource Management - Sukarman, Sukarman; Agustini, Agustini; Alfaina, Nurul (Jurnal Manajemen STIE Muhammadiyah Palopo, 2025)
ABSTRAKPenelitian ini bertujuan mengkaji bagaimana praktik green human resources management dapat mendorong organizational citizenship behavior for the environment (OCBE) di sektor perbankan, dengan lokus penelitian pada bank-bank BUMN yang beroperasi di Kabupaten Kepulauan Selayar, yaitu BRI, BNI, Bank Mandiri, dan BTN. Jenis penelitian yang disebut penelitian asosiatif kausal adalah berbasis kuantitatif. Populasi dalam penelitian ini adalah karyawan Bank BUMN Kabupaten Selayar yaitu: Bank Rakyat Indonesia, Bank Negara Indonesia dan Bank Mandiri dimana jumlah anggota populasi tidak diketahui, responden yang ditentukan dengan teknik convenience sampling dengan total responden Adalah 96. Hasil penelitian menemukan bahwa green training, green performance management, dan green employee involvement terbukti berpengaruh positif dan signifikan terhadap organizational citizenship behavior for the environment (OCBE), sedangkan green reward tidak berpengaruh signifikan. Temuan ini mengindikasikan bahwa perilaku sukarela karyawan dalam mendukung keberlanjutan lebih banyak dipengaruhi oleh aspek pembelajaran, sistem manajemen, serta keterlibatan aktif, daripada sekadar insentif atau penghargaan yang diberikan organisasi.Kata Kunci:Green Training; Green Performance Management; Green Employee Involvement; Organizational Citizenship Behavior for The EnvironmentABSTRACTThis study aims to examine how the practice of green human resources management can encourage organizational citizenship behavior for the environment (OCBE) in the banking sector, with a research locus on state-owned banks operating in the Selayar Islands Regency, namely BRI, BNI, and Bank Mandiri. The type of research called causal associative research is quantitative-based. The population in this study is employees of Bank BUMN Selayar Regency, namely: Bank Rakyat Indonesia, Bank Negara Indonesia and Bank Mandiri where the number of population members is unknown, respondents determined by convenience sampling technique with a total of 96 respondents. The results of the study found that green training, green performance management, and green employee involvement were proven to have a positive and significant effect on organizational citizenship behavior for the environment (OCBE), while green rewards did not have a significant effect. These findings indicate that employees' voluntary behavior in supporting sustainability is more influenced by aspects of learning, management systems, and active engagement, rather than just incentives or rewards provided by organizations.Keywords:Green Training; Green Performance Management; Green Employee Involvement; Organizational Citizenship Behavior for The Environment